Produtividade do trigo irrigado, emissão C-CO2, atributos físicos-hídricos em um latossolo de Cerrado sob diferentes preparos - Silva, Wininton Mendes da (2016)
The development and crops adaptation in atypical areas outside of the normal environment requires the study of many variables that can contribute to the expression of its maximum potential production in the study site. However, soil preparation with mobilization in irrigated areas can impose changes on soil carbon dynamics and increase their loss to the atmosphere as CO2. This study aimed to investigate the effect of soil tillage systems with different mobilization intensities and direct seeding on the irrigated wheat yield in the Cerrado, the dynamics and carbon stocks and CO2 emissions. This experiment was conducted at the experimental station of EMPAER in Tangará da Serra-MT, at 2011 and 2012. The experimental design was randomized blocks in bands, with four replication. Tillage have affect on the irrigated wheat dry matter accumulation in the cerrado, however, does not change the final crop yield, regardless of irrigated blade. The continuous irrigated wheat cultivation reduce the carbon stock in the second cultivation, independent of soil tillage, being important the adoption of conservation management strategies to reduce soil carbon losses with time of cultivation. The soil disturbance during the preparation and increase in irrigation blade are management strategies that increase CO2 emissions in the cerrado, however, the not frequently use of superficial tillage can be used to reduce compaction of irrigated areas without major losses issuing soil carbon.